Shock wave-boundary-layer interactions - Babinsky, Holger; Harvey, John (Cambridge aerospace series., 2011)
"This is the first book devoted solely to the phenomenon of Shock Wave Boundary Layer Interactions and covers all flow regimes where SBLI's occur"--Provided by publisher